In a Man's words - the politics of female representation in the public - Adami, Rebecca (Studier i Pædagogisk Filosofi, 2018)
What one decides fit for appearance through writing and speech bears a political signifi cance that risk being distorted through both language, reception in the public, and through calls for gendered representations. How can work of female philosophers be interpreted as a concern for the world from that of having to respond to a male-dominated discourse through which speech becomes trapped into what one might represent as ‘other’? In this paper, I explore the public reception of two female thinkers who question, in diff erent ways, the dominant notion of the author or philosopher as a male subject; what kind of limitations does the relative notion of ‘female’ pose political action, and how can privilege constitute a hindrance to feminist solidarity?